Youth Labour Markets in Developing and Developed Countries: The Role of the Sectoral Composition of Production - Pramod N. (Raja) Junankar (Institute of Labor Economics (IZA), 2019)
In this paper we explore the role of the sectoral composition of gross domestic product (GDP) in explaining the behaviour of youth labour markets. We provide a comparison of the behaviour of youth unemployment rates, employment-population rates, and labour force participation rates between developing countries and developed (rich) countries. In developing countries, open unemployment is less of a problem: the major problem faced by young people is employment in the informal sector that is poorly paid, intermittent, and insecure. A major part of employment in developing countries consists of "vulnerable employment". After a brief review of the literature, the paper uses panel data to estimate equations for unemployment rates, employment-population rates, and labour force participation rates for youths. We find that the sectoral composition of production and aggregate demand are important in explaining the behaviour of youth labour markets.
Keywords: O11; J21; J46; O17; 330; youth labour markets; sectoral composition; informal employment